Where did the iron go? A case report of a patient with severe iron deficiency anemia despite parenteral and oral iron supplementation due to semaglutide application - Svaguša, Tomo; Šimić, Stjepan; Ćurić, Jure; Sedlić, Filip; Mustapić, Sanda (AME Case Reports, 2026)
Background: Recently, the use of weight loss medications has become increasingly popular. These medications are administered without checking the patient's general condition and potential contraindications.Case Description: Case Description: A 52-year-old patient presents for an emergency check-up due to severe anemia. He has been started weight loss therapy with semaglutide for the past 6 weeks. During the examination, severe sideropenic anemia was verified in the lab (hemoglobin 81 g/L, MCV 70 fL, iron 2 µmol/L, ferritin 10 µg/L). Parenteral and oral iron supplementation was administered at examination. The patient took oral iron daily for the next 6 months while undergoing gastroenterological treatment. He received parenteral iron on three occasions (total 3g), the last parenteral administration immediately after stopping weight loss therapy 6th months after initial examination. A complete gastroenterological examination did not reveal a clear cause of the bleeding. Only after stopping semaglutide did the blood count and tissue iron stores recover. Although the exact mechanism of iron loss is still unknown, it is assumed that its absorption is prevented with increased loss through the mucosa.Conclusions: This case report points to an additional mechanism of iron loss from the body. The aim of this case report is to point out caution when administering weight loss medications to patients who are prone to anemia.